Soluble CD30 as a prognostic factor for outcome following renal transplantation. Issue 7 (26th June 2009) - Platt, R E; Wu, K S T; Poole, K; Newstead, C G; Clark, B
Abstract : Aims: To determine whether measurement of soluble CD30 (sCD30) levels predicts for early rejection in a cohort of first deceased kidney transplant recipients. Methods: Pre-transplant serum samples were analysed for sCD30 levels using a commercial ELISA kit (Biotest). A 100 U/ml cut-off for "high sCD30" was applied. Clinical outcome parameters were biopsy-proven rejection episodes, creatinine levels and glomerular filtration rate. Results: In the cohort of patients who experienced at least one episode of rejection in the first 6 months post-transplant, levels of pre-transplant sCD30 were significantly higher than in those who did not experience rejection. Despite this association, the occurrence of a high sCD30 level did not predict for rejection on an individual basis. Conclusions: The prognostic value of pre-transplant sCD30 testing is diminished by the large number of patients with high sCD30 levels who do not develop rejection. Although this limits the utility of the test in informing clinical management of individual patients, a high pre-transplant sCD30 level should still be considered a risk factor for poorer outcome.